Formation of Filaments and Synthesis of Macromolecules at Temperatures Below the Minimum for Growth of Escherichia coli - Shaw, Maxwell K. (1968)
When Escherichia coli ML30 was transferred during exponential growth at a temperature near the minimum for growth to temperatures just below the minimum for growth, optical density increased for a considerable period of time and considerable synthesis of ribonucleic acid, deoxyribonucleic acid, protein and mucopeptide also occurred. Synthesis of deoxyribonucleic acid was inhibited slightly before the cessation of synthesis of other macromolecules. At 6 C, filaments up to 300 μ in length were formed. Cross walls were not formed, but on transfer to 30 C the filaments rapidly fragmented into short, single cells. The filaments had abundant nuclear material distributed along their length, in contrast to filaments formed by E. coli 15T(−) in the absence of thymine. There was evidence for false division points and incomplete septum formation.